2014
DOI: 10.1097/shk.0000000000000191
|View full text |Cite
|
Sign up to set email alerts
|

Direct Molecular Detection of Pathogens in Blood as Specific Rule-In Diagnostic Biomarker in Patients With Presumed Sepsis

Abstract: The practical value of blood cultures in the diagnosis of sepsis is impaired by a delay in the turnaround time to result and by the fact that blood culture positive can be found for only about 30% of these patients. Conventional laboratory signs of sepsis and acute phase protein biomarkers are sensitive and easy to use, but often also very nonspecific. Molecular diagnostic reflects currently the most promising avenue to decrease time to result and to influence decision making for antibiotic therapy in the sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…45,69,[71][72][73][74][75][76][77][78][80][81][82][83][85][86][87][90][91][92][93][94][96][97][98][99][101][102][103]107,[109][110][111][112]114 Of these, nine studies reported blood volumes that did not comply with CE approval: Lehmann et al, 76 Lodes et al 92 and von Lilienfeld-Toal et al 71 all reported using 1 ml in adults; Bloos et al, 74 Lamoth et al, 75 Paolucci et al 99 and Sitnik et al 107 all reported using 3 ml in adults; Berger et al…”
Section: Details Of Index and Reference Tests Blood Sampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…45,69,[71][72][73][74][75][76][77][78][80][81][82][83][85][86][87][90][91][92][93][94][96][97][98][99][101][102][103]107,[109][110][111][112]114 Of these, nine studies reported blood volumes that did not comply with CE approval: Lehmann et al, 76 Lodes et al 92 and von Lilienfeld-Toal et al 71 all reported using 1 ml in adults; Bloos et al, 74 Lamoth et al, 75 Paolucci et al 99 and Sitnik et al 107 all reported using 3 ml in adults; Berger et al…”
Section: Details Of Index and Reference Tests Blood Sampling Methodsmentioning
confidence: 99%
“…Twenty-one SeptiFast studies reported data on the time to availability of results/pathogen identification. [44][45][46]59,60,64,68,69,77,80,81,85,88,93,96,97,101,106,107,110,112 However, for the majority of these studies, it was unclear if the value was the mean or median, and variance estimates or ranges were not reported. Across these studies, the reported time to pathogen identification with SeptiFast ranged from 4 hours 68 to a median of 26.25 hours [range 6.75-79 hours (for samples collected at beginning of a weekend)].…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
“…Meta-analyses for testing molecular detection of pathogen in the blood have reported these tests as less sensitive and less specific than BCs, taken as the gold standard, and consequently these tests are rarely used in the diagnostic standard workup [19, 20]. It should be noted that in the previous studies, many cases were shown with positive molecular tests and BC-negative with clinical status showing signs of bloodstream infections [21, 22]. The cost-effectiveness of molecular direct testing in blood remains unknown [23].…”
Section: Introductionmentioning
confidence: 99%
“…They are found primarily in fresh and brackish water. They can cause infections ranges from mild cellulitis to ecthyma gangrenosum and even sepsis in immunocompromised patients [6].…”
Section: Discussionmentioning
confidence: 99%